"The Only Actual Theology of the Whole Torah": Rosenzweig on the Divine Name, the Divine Attributes, and the Space of Redemption - Pollock, Benjamin (The journal of Jewish thought & philosophy, 2025)
To explain what Rosenzweig means when he identifies Exodus 33-34 as "the only actual theology of the whole Torah," I undertake a close reading of Rosenzweig’s comments on Exodus 33-34 in the Working Papers (Arbeitspapiere) and compare them with his parallel discussion of Exodus 3:14 with Buber. I argue that if we are to make sense of the way Rosenzweig would have us understand the relationship between worldly space, the divine name, and the divine attributes, we must revisit his early formulations of his notion of revelation as orientation.